Sistem Pendukung Keputusan Pemilihan Jurusan Menggunakan Metode SAW Pada SMK Negeri 2 Sarolangun - Rawal Dewa, Suhendra; Jasmir, Jasmir (Jurnal Manajemen Sistem Informasi, 2023)
The selection of majors at SMK Negeri 2 Sarolagun has difficulties with the new student registrationcommittee because the data for prospective students is quite a lot and the time available for processingdata is limited and processing values for each field is still using a manual system, using MicrosoftSuperior. For this reason, a support system for the selection of majors at SMK Negeri 2 Sarogun isneeded. Where the results and discussion in this Decision Support System are based on research thatis generally carried out in the process of selecting majors. The purpose of this research is to analyzeand design a decision support system for majors selection using the SAW (Simple Additive Weighting)method and using the UML (Unified Modeling Language) modeling tool. This research produces aprototype that can be implemented further into a system so as to produce a decision support system forthe selection ofmajors in SMK Negeri 2 Sarolangun.